The Martyrs of Columbine - Watson, J. author. aut Link
XII, 212 p.
Keywords: On April 20, 1999, Eric Harris and Dylan Klebold killed twelve fellow students and one teacher at Columbine High School in Littleton, Colorado. Two of the victims of the Columbine massacre, Cassie Bernall and Rachel Scott, reportedly were asked by the gunmen if they believed in God. Both supposedly answered 'Yes' and were killed. Within days of their death, Cassie and Rachel were being hailed as modern-day martyrs and are seen by many American evangelicals as the sparks of a religious revival among teenagers. Cassie and Rachel, as innocents martyred for faith, also became useful symbols for those seeking to advance a conservative political agenda and to lay the blame for Columbine at the feet of their liberal opponents. According to police investigators, however, Cassie and Rachel may never have been asked by their killers about God. They may have been simply victims of a senseless crime rather than martyrs to a cause. The Martyrs of Columbine provides a careful examination of the available evidence and attempts to discover what really occurred. Despite these questions the martyr-stories continued to be told and the religious and political use of Cassie and Rachel continues. The popular significance of the martyrs of Columbine persists, and may even be growing. How and why is this happening? The Martyrs of Columbine is a groundbreaking investigation of what this tragedy has come and will come to mean in American religion, politics, and culture.